Cost of goods sold analysis and recommendations to reduce costs of co-packaged mifepristone-misoprostol for medical abortion - Lester Chinery; Chadia Allaouidine; Alessandra Tomazzini; Melanie Larson; A. Metin Gülmezoglu (BMC, 2020)
Abstract Objective Understanding the price components of the mifepristone/misoprostol (combi-pack) for medical abortion to improve access is critical for identifying strategies to reduce product costs for quality-assured formulations and expanding its availability and use. Methods We constructed a cost of goods sold analysis using data collected from manufacturing companies in Bangladesh, China and India supported by publicly available information related to the product formulation, active pharmaceutical ingredients (API), manufacturing location, manufacturer profiles and other individual model components. Key model components were the active pharmaceutical ingredients (quality-assured or not), excipients, labour cost, operating cost and packaging. Results Combi-pack direct production cost ranges from US$1.08 for finished products which are not quality assured to US$3.05 for products containing quality assured active pharmaceutical ingredients, which means that with a 30% administrative fee applied to those prices, it could be made available between US$1.40 and US$3.97 depending on location, manufacturer's profile, optimal market situation and the quality of the active pharmaceutical ingredients. The main model component impacting on the cost range is the purchase price of mifepristone active pharmaceutical ingredient and the current differential between quality-assured material supported by adequate documentation and API for which quality assurance cannot be demonstrated. Compared to India cost of goods sold is lower in Bangladesh primarily due to lower operating costs, including the cost of labour. Conclusions It is feasible to lower the cost of quality-assured combi-packs, through reducing mifepristone API cost and selection of the manufacturing location. However, manufacturers need to be incentivised to achieve WHO pre-qualification with a carefully built business case and require support in identifying and sourcing competitively priced material and manufacturing products to the necessary standard.